Species-specific detection of environmental DNA by endpoint PCR using mismatch base introducing primer design and nested PCR - Ishii, Ryosuke; Poti, Teeranai; Akimitsu, Kazuya; Narumi-Kawasaki, Takako; Yamada, Yoshihiro (My University, 2025)
Environmental DNA (eDNA) has been used effectively for species identification in aquatic macrobiological surveys. To popularize this method, a cost-effective analysis method with high sensitivity is required. In this study, we developed an eDNA detection method that is as sensitive as conventional quantitative real-time PCR (qPCR), which does not require expensive equipment, and with heightened sensitivity that was achieved through mismatch-introducing primer design and nested PCR. The subject of the experiment was Micropterus nigricans (largemouth bass). Standard PCR with mismatch-free primers detected amplicons not only in M. nigricans but also in M. dolomieu and Lateolabrax japonicus. However, the mismatched primers only amplified DNA from M. nigricans and did not show amplicons for the non-target species. Endpoint PCR was less sensitive than qPCR, but it was able to specifically detect the target species in environmental samples. A similar approach was applied to the bitterling fish species, a species to which many other closely related species are known, and Acheilognathus cyanostigma eDNA was specifically detected. This eDNA analysis method is cost-effective because it is comparable in sensitivity to conventional qPCR methods and does not require expensive equipment.
Keywords: Conservation; eDNA; Electrophoresis; Endangered species; Invasive species